Identification of planck’s constant by Light Emitting Diodes (LEDS) / Nurain Azmi ... [et al.] - Azmi, Nurain; Mustafa, Sabirin; Mohd Yunos, Nur Hazirah; Wan Mohd Sakri, Wan Nor Azlin; Abdul Halim, Muhammad Nazzim; Aadenan, Amin (Universiti Teknologi MARA, Negeri Sembilan, 2020)
In this paper, a simple analysis yet a straight forward method of determining the Planck’s constant by evaluating the stopping potential of five different colors of light emitting diodes (LEDs) is presented. The study aimed to identify the Planck’s constant based on the relationship between the potential difference of LEDs to their respective frequencies under room temperature with low illumination of ambient light by applying a simple theoretical analysis. The experiment was performed by connecting the circuit in series connection and the voltage reading of LEDs were recorded and then presented in a graph of frequency, f versus stopping voltage, Vo. To determine the Planck’s constant, the best fit line was analyzed and the centroid was also identified in order to find the minimum and maximum errors due the gradient of the graph. From the analysis, results showed that the Planck constant value was (5.997 ± 1.520) × 10–34 J.s with approximately 10% of deviation from the actual value. This demonstrates that a simple analysis can be utilized to determine the Planck’s constant for the purpose of the laboratory teaching and learning at the undergraduate level and can be served as a starting point for the students to understand the concept of quantization of energy in Modern Physics more effectively. This is to further suggest that the Planck’s constant can be identified via a low-cost and unsophisticated experimental setup.